Four new araneogenous species and a new genus in Hypocreales (Clavicipitaceae, Cordycipitaceae) from the karst region of China - Wan-Hao Chen; Dan Li; Hui-Lin Shu; Jian-Dong Liang; Jie-Hong Zhao; Wei-Yi Tian; Yan-Feng Han (MycoKeys)
The karst region in southwestern China is one of the biodiversity hotspots in the world with rich fungal diversity but under-studied. Four fungal species belonging to Chlorocillium (Clavicipitaceae) and Gamszarella (Cordycipitaceae) were isolated from dead spiders. Morphological comparisons, phylogenetic analyses and a PHI analysis based on multigene datasets support the establishment of these new species viz., Chlorocillium guizhouense sp. nov., C. vallense sp. nov., Gamszarella sinensis sp. nov., and G. vallensis sp. nov. are introduced. A new genus, Neogamszarella, is proposed to accommodate Gamszarella antillana, which is phylogenetically distinct from Gamszarella s. str. Our results revealed that further attention needs to be paid to the diversity of araneogenous fungi in the karst regions of southwestern China.